2017
DOI: 10.1177/1039856217715997
|View full text |Cite
|
Sign up to set email alerts
|

Zoophilia in an adolescent with high-functioning autism from Sri Lanka

Abstract: We postulate that his persistent social difficulties contributed to the development of a paraphilic disorder. Unlike with his RRBs, he was markedly distressed about this sexual behaviour. Further research is required to explore this rarely reported, potential association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Only one article was identified as being relevant in the present review (Chandradasa & Champika, 2017), three further articles included a description of a case involving someone with ASD who engaged in zoophilia or bestiality (Jones, 2007;Freckelton, 2013;Kellaher, 2015) and another paper, although not the focus of the study, found one person with AD who had several paraphilias including olfactophilia, podophilia and zoophilia in a sample of 20 institutionalized, male adolescents and young adults with Autistic Disorder (AD) and borderline/mild mental retardation (MR) (Hellemans, Roeyers, Leplae, Dewaele, & Deboutte, 2010). The relevant information will be discussed in turn.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one article was identified as being relevant in the present review (Chandradasa & Champika, 2017), three further articles included a description of a case involving someone with ASD who engaged in zoophilia or bestiality (Jones, 2007;Freckelton, 2013;Kellaher, 2015) and another paper, although not the focus of the study, found one person with AD who had several paraphilias including olfactophilia, podophilia and zoophilia in a sample of 20 institutionalized, male adolescents and young adults with Autistic Disorder (AD) and borderline/mild mental retardation (MR) (Hellemans, Roeyers, Leplae, Dewaele, & Deboutte, 2010). The relevant information will be discussed in turn.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, Chandradasa and Champika (2017) had intelligence and academic abilities within the normal range. The amount of time that SB was spending at his grandparents' cattle house had been increasing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Kinsey et al (, ) found that individuals who have sex with animals may be more educated than the general population, with close to half of their subjects with a history of bestiality reporting that they had obtained a college degree. Case reports have variously documented the occurrence of human–animal sexual acts in individuals with autism (Chandradasa & Champika, ); alcohol use (Satapathy, Swain, Pandey, & Behera, ); depressive disorder, schizoaffective disorder, and antisocial personality disorder (Holoyda, ); and transvestism and pedophilia in the context of mania (Mendhekar & Mehta, ). Lesandric, Orlovic, Peitl, and Karlovic () wrote about a case of zoophilia in a young man who had sex with a cow in his early teens, persistent zoophilic fantasies throughout his teen years, then another episode of intercourse with a cow in his early 20s, before ultimately decompensating into psychosis.…”
Section: Clinical Considerationsmentioning
confidence: 99%